Women and men in CARICOM member states : power and decision making 1980-2002 (CCS GeorgetownGY, 2003)
Indicates the status of the situation in Member States with respect to the nature of the inequality that exists in specific areas of the policy and decision-making process. Provides an estimate of how close the region is to achieving the goal of 30 percent participation of women in decision-making by 2005. Includes tables on - Parliamentary Assemblies; public order; safety occupations; senior level positions in the government service and managerial and other professional occupations.
Keywords: WOMEN